solve for F in the formula i/p + i/f = i/c show work please?

1 Answer

Relevance
  • 7 years ago
    Best Answer

    i/p + i/f = i/c

    By Least Common Factor,

    (if+ip)/pf=i/c

    By Crossmultiplying,

    ifc+ipc=ipf

    Rearranging the above equation,

    ifc-ipf=(-ipc)

    Taking i and f common from LHS of above equation,

    i*f*(c-p) = i*(-pc)

    Eliminating i on both sides,

    f*(c-p) = -pc

    Hence, f = -pc/(c-p)

    or f = pc/(p-c)

Still have questions? Get your answers by asking now.